2003
DOI: 10.1177/030089160308900308
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary Small Cell Carcinoma: Multimodality Treatment Results

Abstract: Treatment results for extrapulmonary small-cell carcinoma are comparable to those of small-cell carcinomas of the lung. Extent of disease is a significant prognostic factor for survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 28 publications
(4 reference statements)
5
39
2
1
Order By: Relevance
“…Female gender, a favorable prognostic factor not mentioned in previously published studies, may partly be attributable to tumors of gynecologic origin, which were often associated with a better outcome than tumors of other origins [12, 15]. Several groups of investigators have pointed out that limited disease is the most sensitive predictor of better survival [15,16,17]. Further, Sevin et al[ 18] reported that combined modality treatment provided the best chance of survival in patients with EPSCC of gynecologic origin [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female gender, a favorable prognostic factor not mentioned in previously published studies, may partly be attributable to tumors of gynecologic origin, which were often associated with a better outcome than tumors of other origins [12, 15]. Several groups of investigators have pointed out that limited disease is the most sensitive predictor of better survival [15,16,17]. Further, Sevin et al[ 18] reported that combined modality treatment provided the best chance of survival in patients with EPSCC of gynecologic origin [18].…”
Section: Discussionmentioning
confidence: 99%
“…All six studies reported a predominance of patients with limited disease. The distribution of the cancer origin varied, but gastrointestinal origin seemed to be the most common site and associated with the worst prognosis in five of the six studies [1, 11, 12, 15, 17]. Because these studies differed in sample sizes and were retrospective in design, survival outcome was hard to compare.…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases have been reported till date [3,4,[5][6][7][8][9][10][11][12][13][14][15]. Neuroendocrine tumors arise from embryonic neural crest cells that migrate to bronchopulmonary or gastrointestinal tract during development.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical progression was rapid, and death occurred within five months after diagnosis. Sengoz et al [9] reported two cases; one patient received chemotherapy whereas hemihepatectomy was performed on another. The survival of the patients was 13 and 67 months respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Şengöz ve ark. [14] retrospektif olarak değer-lendirdikleri 16 ekstrapulmoner yerleşimli hastalarda 2 ve 5 yıllık sağkalımları sırasıyla %41 ve %11 olarak bildirmişlerdir. Ortalama sağkalım ise 14 ay olarak bildirilmiştir.…”
Section: Discussionunclassified